Intramyometrial ectopic pregnancy following in vitro fertilization. Conservative treatment with intrasaccular methotrexate followed by successful pregnancy after thawed embryo transfer - F. Rechkemmer, Adolfo (2022)
We describe a case of ectopic intramyometrial pregnancy after in vitro fertilizationand embryo transfer (IVF-ET), treated conservatively by ultrasound-guidedintrasacular injection of methotrexate, followed by a successful twin pregnancy afterfrozen-thawed embryos transfer.